2009
DOI: 10.1016/j.foodcont.2008.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular enzyme production and enterotoxigenic gene profiles of Bacillus cereus and Bacillus thuringiensis strains isolated from cheese in Turkey

Abstract: a b s t r a c tThe aim of the present study was to investigate the biochemical characteristics, extracellular enzyme production and enterotoxigenic genes contents of 6 Bacillus cereus and 22 Bacillus thuringiensis strains, isolated from 100 cheese samples in Turkey. Crystal morphologies of B. thuringiensis strains were found either spherical (n = 12) or spherical and irregular-shaped (n = 10) by phase contrast microscopy. B. cereus and B. thuringiensis strains were found to produce extracellular enzymes, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 61 publications
6
37
1
Order By: Relevance
“…cereus contamination has been determined previously by Ozdemir [30] , in pasteurised milk samples and was isolated from 56 (46.6%) of the samples. Molva et al [31] , also detected B. cereus from 6% of cheese samples.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…cereus contamination has been determined previously by Ozdemir [30] , in pasteurised milk samples and was isolated from 56 (46.6%) of the samples. Molva et al [31] , also detected B. cereus from 6% of cheese samples.…”
Section: Discussionmentioning
confidence: 94%
“…In the detection of enterotoxin genes, 30% of B. cereus strains were found to carry the three hbl genes. Molva et al [31] , found that all detected strains contained hblD gene. Hansen and Hendriksen [33] , reported that 64% of B. cereus strains contained this gene.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The extracellular production of enzymes among Bacillus spp. is common (Priest 1977;Molva et al 2009). Some endoglucanase activity was also detected as intracellular and membrane-bound when B. aerius S5.2 was grown on both substrates; however, this expression was minimal compared with extracellular production.…”
Section: Localization Of Endoglucanase On Cmc and Msmentioning
confidence: 99%
“…In Algeria B. cereus is not researched as poisoning causal bacterium due to dairy products. So far, few or rare works have reported B. cereus and its toxins in processed cheese while some works have studied this bacterium on cheddar cheese, raw material used for manufacturing of processed cheese (Molva et al, 2009;Cherif-Antar et al, 2015 (Upasana and Labbé, 2016).…”
Section: Author(s) Agree That This Article Remains Permanently Open Amentioning
confidence: 99%